Validation of Analytical Method for Vitamin A in Bioadhesive Ocular Cationic Nanoemulsion Loaded into Thermosensitive Gel Using RP-HPLC - Fatimah, Siti Fatmawati; Lukitaningsih, Endang; Martien, Ronny; Nugroho, Akhmad Kharis (Indonesian Journal of Chemistry, 2024)
Various test methods have been previously documented for determining vitamin A levels in different dosage forms. This study specifically examines an isocratic reverse phase-high performance liquid chromatography (RP-HPLC) method designed for the direct extraction of vitamin A. The objective is to validate an analytical method for quantifying vitamin A in bioadhesive cationic nanoemulsions incorporated into thermosensitive gels. The method employs isocratic RP-HPLC with a YMC-Triart C18 column (L1), dimensions of 4.6 mm × 250 nm, particle size of S-5 µm, and a UV detector at λ = 265 nm. The mobile phase consists of HPLC-grade methanol, acetonitrile, and n-hexane in a ratio of 46.5:46.5:7. Validation parameters were assessed including selectivity, linearity, accuracy, precision, limit of quantification (LOQ), and limit of detection (LOD). Correlation coefficients were determined with an R2 value of 0.9995 in the concentration range of 264–396 μg/mL (w/v). Recovery percentages ranged from 99.295% to 99.878%. Repeatability and intermediate precision relative standard deviations (RSD) were found to be 0.318% and 0.254%, respectively. The LOD was established at 2.018 μg/mL, and the LOQ was determined to be 6.114 μg/mL. The results affirm cost-effective and well-suited for the accurate measurement of vitamin A levels in bioadhesive thermosensitive gel formulations.